Collapse query cause: the management of adult syncope in the emergency department. Issue 8 (20th July 2006) - Reed, M J; Gray, A
Abstract : Syncope is a commonly encountered problem in the emergency department (ED). Its causes are many and varied, some of which are potentially life threatening. A review was carried out of relevant papers in the available literature, and this article attempts to assimilate current evidence relating to ED management. While the cause of syncope can be identified in many patients, and life threatening conditions subsequently treated, a risk stratification approach should be taken for those in whom a cause is not identified in the ED. Aspects of the history and examination that may help identify high risk patients are explored and the role of investigations to aid this stratification is discussed. Identifying a cardiac cause for syncope is a poor prognostic indicator. Patients with unexplained syncope who have significant cardiac disease should therefore be investigated thoroughly to determine the nature of the underlying heart disease and the cause of syncope, although presently there is little evidence that this improves their dismal prognosis. This risk stratification approach has led to the development of several clinical decision rules, which are discussed along with current international guidelines on syncope management. This review suggests that presently the American College of Emergency Physicians guidelines are the most useful aids specific to the management of syncope in the ED; however, the Osservatorio Epidemiologico sulla Sincope nel Lazio (OESIL) score may also be a useful ED risk stratification tool